A general strategy to ultrasensitive Ga2O3 based self-powered solar-blind photodetectors. (March 2022) - Wu, C.; Wu, F.; Ma, C.; Li, S.; Liu, A.; Yang, X.; Chen, Y.; Wang, J.; Guo, D.
Abstract: Ga2 O3 based self-powered photodetectors, which can work in photovoltaic mode, show great potential applications in the next-generation photodetectors. Due to the difficulty of p-type doping of Ga2 O3, constructing heterojunctions is a promising alternative for self-powered Ga2 O3 photodetectors. Although several inorganic materials have been focused on fabricating Ga2 O3 based heterojunction, some disadvantages prevent them from being widely used, such as the large lattice mismatch, the unsuitable bandgap, the inflexibility, the complex preparation process, etc. In this study, a general strategy has been proposed for high-performance photodetectors through building a type-Ⅱ Ga2 O3 heterojunction with the small-molecule hole transport materials (SMHTMs). The relatively large hole mobility of SMHTMs guarantees the high-speed transport of the photogenerated holes, and the solar-blind filter effect of the SMHTMs films makes the photodetector highly spectrum selective. Herein, four types of SMHTMs have been used to constructed photodetectors with Ga2 O3, and all of them exhibit self-powered characteristics with I on / I off ratios of about>10 5, which is 1–2 orders of magnitude larger than these previously reported Ga2 O3 photodetectors. Among them, the photodetector based on β -Ga2 O3 /TAPC heterojunction shows the best photoelectrical performances with a dark current of about 20 fA, a I on / I off ratio of 5.9 × 10 5, and a detectivity of 1.02 × 10 13 Jones at 0 V, all of which are amongst the best values ever reported for Ga2 O3 based self-powered photodetectors. The high-speed transport of the photogenerated holes and large built-in field in the β -Ga2 O3 /SMHTMs heterojunctions should be responsible for these remarkable performances. This work provides a feasible strategy to high-performance Ga2 O3 based self-powered photodetectors, thus may push forward their applications. Graphical abstract: Thanks to the relatively large hole mobility and the solar-blind filter effect of the small-molecule hole transport materials (SMHTMs), the β -Ga2 O3 /SMHTMs based self-powered solar-blind photodetectors exhibit excellent I on /I off ratios and spectrum selective. Image 1 Highlights: Triphenylamine (TPA)-based small molecule HTMs have been first used in the solar-blind photodetector field. The SMHTMs film demonstrates a weak absorption in 200–280 nm, showing the ''solar-blind filter'' effect. All the photodetectors in our work exhibit self-powered characteristics with extremely high Ion / Ioff ratios (> 10 5 ). Taking advantage of its high wavelength selectivity and Ion /Ioff ratio, we designed a solar-blind communication system.